2009
DOI: 10.1136/thx.2009.117572
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index is associated with the development of acute respiratory distress syndrome

Abstract: Background: The relationship between body mass index (BMI) and development of acute respiratory distress syndrome (ARDS) is unknown. Methods: A cohort study of critically ill patients at risk for ARDS was carried out. BMI was calculated from admission height and weight. Patients were screened daily for AECC (American European Consensus Committee)-defined ARDS and 60-day ARDS mortality. Results: Of 1795 patients, 83 (5%) patients were underweight (BMI ,18.5 kg/m 2 ), 627 (35%) normal (BMI 18.5-24.9), 605 (34%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
249
1
11

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(273 citation statements)
references
References 34 publications
12
249
1
11
Order By: Relevance
“…Previous studies have shown that obesity is associated with the development of ARDS. 31,32 However, a recent French study found the use of prone positioning to be safe in obese subjects, and prone positioning improved oxygenation more in obese subjects with ARDS than in non-obese subjects. 33 Our study has several important limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that obesity is associated with the development of ARDS. 31,32 However, a recent French study found the use of prone positioning to be safe in obese subjects, and prone positioning improved oxygenation more in obese subjects with ARDS than in non-obese subjects. 33 Our study has several important limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators, although not all, believe that obese children have higher morbidity and mortality. [2][3][4] In adults, higher BMI is associated with the development of acute respiratory distress syndrome (ARDS) 5 ; for those developing ARDS, increasing BMI was associated with prolonged stay. However, increased BMI was not associated with increased mortality.…”
mentioning
confidence: 99%
“…Volume 5 that is not matched with a greater mortality [15,16]. As mentioned, this unexplained finding has been called the obesity-ARDS paradox [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…The obesity paradox usually refers to the unexplained decreased overall mortality and decreased mortality from cardiovascular events in otherwise healthy mildly obese patients compared to normal weight patients [7,10,11]. Repeated studies report a decreased incidence and/or reduced mortality from the acute respiratory distress syndrome (ARDS) [12][13][14][15] in obese patients compared to normal weight individuals, although a few conflicting findings exist [15,16]. In addition, obesity has been associated with a delayed ARDS onset during an ICU stay [15] and lower plasma inflammatory markers during ARDS development [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation